2020
DOI: 10.1186/s12880-020-00436-9
|View full text |Cite
|
Sign up to set email alerts
|

The independent indicators for differentiating renal cell carcinoma from renal angiomyolipoma by contrast-enhanced ultrasound

Abstract: Background: The value of contrast-enhanced ultrasound (CEUS) in differentiating between renal cell carcinoma (RCC) and angiomyolipoma (AML) was analyzed. The purpose of this study was to identify the independent indicators of CEUS for predicting RCC. Methods: A total of 172 renal tumors (150 RCCs, 22 AMLs) in 165 patients underwent conventional ultrasound (CUS) and CEUS examinations before radical or partial nephrectomy, and the features on CUS and CEUS were analyzed. Results: There were significant difference… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
1
12
2
Order By: Relevance
“…In addition, our previous study of 172 renal masses (150 RCCs and 22 AMLs) showed significant difference in PRE between RCCs and AMLs on CEUS (76.7% vs. 9.1%,P = .000). 14 Compared with the above studies, PRE presented at a higher rate (80.9%, 106/131) in this study, which may be due to the small size of the masses (≤4 cm). Previous study showed that the presence of mass pseudocapsule was related to the tumor size of RCCs, with a substantially higher prevalence in tumors of size 2.1-5 cm than in tumors of other sizes.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In addition, our previous study of 172 renal masses (150 RCCs and 22 AMLs) showed significant difference in PRE between RCCs and AMLs on CEUS (76.7% vs. 9.1%,P = .000). 14 Compared with the above studies, PRE presented at a higher rate (80.9%, 106/131) in this study, which may be due to the small size of the masses (≤4 cm). Previous study showed that the presence of mass pseudocapsule was related to the tumor size of RCCs, with a substantially higher prevalence in tumors of size 2.1-5 cm than in tumors of other sizes.…”
Section: Discussioncontrasting
confidence: 68%
“…In one of our previous studies, we found that hyperenhancement (64/81, 79.0%), homogeneous enhancement (54/81, 66.7%), fast wash out (WO) (63/81, 77.8%), and peripheral rim‐like enhancement (PRE) (45/81, 55.6%) were the typical characteristics of small RCC (≤3.0 cm) 8 . In a more recent study, we found that PRE and fast WO are important indicators for predicting RCC 14 . However, we did not consider the factors responsible for RCC subtypes in both studies and the size of renal mass in the second study.…”
mentioning
confidence: 92%
“…Or it can also be explained that when the tumor size exceeds 4 cm, it always invades the renal capsule and infiltrates into perirenal fat so the pseudocapsule is disrupted or even absent. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the presence of perilesional rim-like enhancement, commonly defined as pseudocapsule, results from tumor growth producing compression, ischemia, and necrosis of adjacent normal tissue, and consequent change in fibrous tissue. Notably, this sign was useful in discriminating malignancy among other historical series [ 18 , 19 ]. However, it should be taken into account that the presence of pseudocapsule could be inversely related to the tumor size of RCCs and is usually absent in hemorrhagic cysts and angiomyolipomas [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%